2019
DOI: 10.1038/s41545-018-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale remediation of oil-contaminated water using floating treatment wetlands

Abstract: The contamination of water with hydrocarbons resulting from oil exploration and production highlights the need for efficient and environmentally friendly technology to mitigate this form of water pollution. Floating treatment wetlands are a sustainable approach for remediating contaminated water. In this large-scale study, we used four different plants, Phragmites australis, Typha domingensis, Leptochloa fusca, and Brachiaria mutica, to vegetate a floating mat with an area of 3058 m 2 made from locally sourced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 63 publications
(91 reference statements)
1
44
0
Order By: Relevance
“…This finding is consistent with previous studies in which inoculated bacteria improved the pollutant removal process [24,34]. The survival of inoculated bacteria depends upon the nutrient supply, pH, temperature and the interaction with the host [56,57]. In this study, the bacterial population in the roots and shoots of inoculated plants were found to be higher as compared to non-inoculated vegetated treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with previous studies in which inoculated bacteria improved the pollutant removal process [24,34]. The survival of inoculated bacteria depends upon the nutrient supply, pH, temperature and the interaction with the host [56,57]. In this study, the bacterial population in the roots and shoots of inoculated plants were found to be higher as compared to non-inoculated vegetated treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Further, these bacteria were initially isolated from the roots and shoots of the plants; hence these bacteria possibly have an adaptive mechanism to survive and grow in these parts of the plant in this hostile environment [18,27]. In order to make FTWs a potential wastewater treatment method, periodic inoculation of bacteria should be performed in order to overcome the problem of decreasing bacteria with time in inoculated water [57,59].…”
Section: Discussionmentioning
confidence: 99%
“…The root provides sufficient surface area for the attachment and colonization of various microorganisms. Roots also release different exudates like citrate, oxalate, amino acid, malate, etc., which act as a carbon source for the microbes and helps in their stimulation and proliferation [16,[24][25][26]38]. As the microbial population increases, the biofilm layer becomes sticky in nature.…”
Section: Pollutants Removal Mechanism In Efbmentioning
confidence: 99%
“…Bioremediation is an effective, cost-saving, and eco-friendly approach to re-establishing deteriorated environments [5]. There are several types of bioremediation, including microbial remediation (microbes), phytoremediation (plants), and mycoremediation (fungi) [6][7][8]. The meaning and implementation of each bioremediation type are totally different from one another in terms of mechanism.…”
Section: Introductionmentioning
confidence: 99%